2021
DOI: 10.3390/cancers14010181
|View full text |Cite
|
Sign up to set email alerts
|

Bak and Bcl-xL Participate in Regulating Sensitivity of Solid Tumor Derived Cell Lines to Mcl-1 Inhibitors

Abstract: BH3 mimetics represent a promising tool in cancer treatment. Recently, the drugs targeting the Mcl-1 protein progressed into clinical trials, and numerous studies are focused on the investigation of their activity in various preclinical models. We investigated two BH3 mimetics to Mcl-1, A1210477 and S63845, and found their different efficacies in on-target doses, despite the fact that both agents interacted with the target. Thus, S63845 induced apoptosis more effectively through a Bak-dependent mechanism. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Similarly, APG115 can synergistically promote apoptosis of ibrutinib by promoting MCL-1 degradation 45,47,48 . The current potential application direction of APG115 is cooperating with cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, APG115 can synergistically promote apoptosis of ibrutinib by promoting MCL-1 degradation 45,47,48 . The current potential application direction of APG115 is cooperating with cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…P53 binds to MCL-1 and promotes ubiquitination, which is then transferred to proteasome degradation. The decreased expression of MCL-1 promotes apoptosis by up-regulating downstream apoptotic molecules PUMA and NOXA [43][44][45] . Additionally, the PUMA and NOXA further enhances the functions of the pro-apoptotic proteins BAX and BAK.…”
Section: Discussionmentioning
confidence: 99%
“…However, free Bak can be recaptured by Bcl-xL, leading to a resistance to A1210477 [ 115 ]. Similarly, S63845-induced apoptosis occurs in a Bak-dependent manner in solid tumor-derived cell lines [ 116 ]. S64315 enhances the selective senolytic effect of ABT-263 and ABT-737.…”
Section: The Bcl-2 Family Proteins As a Target For Senolytic Agentsmentioning
confidence: 99%
“…Still, in the same study, the authors translated those findings to animal models, in which they found that the addition of the Bcl-xL inhibitor to 5-FU caused the strongest anti-tumoral effect, proving support for association therapies. Several studies with a focus in tumor cells state that a Bcl-xL inhibitor as a single agent is not adequate to promote apoptosis [39]. There are reports in cancer cells and animal models, that the use of BTSA1.2 (an orally bioavailable Bax activator) in combination with Bcl-xL has a synergist anti-tumoral effect while being safe for healthy tissues [39,40].…”
Section: Cancers With Frequent Bcl-2 Alterationsmentioning
confidence: 99%
“…Several studies with a focus in tumor cells state that a Bcl-xL inhibitor as a single agent is not adequate to promote apoptosis [39]. There are reports in cancer cells and animal models, that the use of BTSA1.2 (an orally bioavailable Bax activator) in combination with Bcl-xL has a synergist anti-tumoral effect while being safe for healthy tissues [39,40]. This mechanism in which solid tumors rely on Bcl-xL for survival has led to several studies focusing on selective Bcl-xL inhibitors [41].…”
Section: Cancers With Frequent Bcl-2 Alterationsmentioning
confidence: 99%